Pengaruh Model Pembelajaran Somatic, Auditory, Visualization, Intellectual (SAVI) Terhadap Spatial Thinking Peserta Didik Pada Mata Pelajaran Geografi Kelas XI IPS SMA Islam 1 Surakarta Tahun 2021/2022 - Siti Murwani; Sugiyanto Sugiyanto; Gentur Adi Tjahjono (Universitas Sebelas Maret (UNS), 2025)
This study stems from the problem of students' low spatial thinking skills in geography learning, particularly on the topic of natural disaster mitigation. The main objective of this study is to analyze the effect of implementing the Somatic, Auditory, Visualization, and Intellectual (SAVI) learning model on improving spatial thinking skills. The study used a quasi-experimental method with a nonequivalent control group design. The sample consisted of two eleventh grade social studies classes at SMA Islam 1 Surakarta, where the experimental class implemented the SAVI model, while the control class used expository learning. Data were obtained through pre-tests and post-tests as well as observation sheets. The results showed that SAVI learning combined with the use of maps significantly improved spatial thinking skills based on five indicators: comparison, aura, region, hierarchy, and association. Overall, this study demonstrates that the SAVI approach can develop students' spatial skills through the use of various sensory stimuli and direct learning experiences an approach previously rarely used in natural disaster mitigation materials. Based on these findings, the SAVI model is recommended as an alternative to active and contextual learning in geography education.